First observation on mating and reproductive seasonality in maned sloths Bradypus torquatus (Pilosa: Bradypodidae) - Dias, Bernardo B; Dias dos Santos, Luis Alberto; Lara-Ruiz, Paula; Cassano, Camila Righetto; Pinder, Laurenz; Chiarello, Adriano G (Journal of ethology, 2009)
Information on mating season is of paramount importance for our understanding of reproductive behavior, yet little is currently known about the breeding season of Xenarhtra as a whole and sloths in particular. A pair of maned sloths was observed copulating in September 2005 in the Atlantic Forest region of south-eastern Brazil. Our studies on mating of the manned sloth as well of other hitherto unpublished records of newborn sloths seen in the wild, together with a review of previous information, indicate that B. torquatus is a seasonal breeder. Infants are born predominantly at the end of the wet season and beginning of the dry season (February-April), and copulation concentrates in the late dry and early wet seasons (August-October). This strategy allows for the energy-demanding gestation and lactation to take place during the less stressful period of the year.